Program Kota Tanpa Kumuh (Kotaku) Dalam Perspektif Pemberdayaan Masyarakat (studi kasus Program Kota Tanpa Kumuh di Kelurahan Karangwaru) - KHOLQI, AHSANUL; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2020)
The Urban slams appeared because of inability or failure of the public to compete aachieve and have all the needs to support life's necessities. The existence of slums could becaused by the development of the city. Because of that, community development can bealternative solution to complete the problem of slums in Indonesia. Empowerment is a conceptfor giving people's big responsbility about how to work. "Kotaku" Program means to build anintegrated system for slum management, which is local governments lead and collaborate withstakeholders in planning and implementation, as well as promoting community participation.One that has been addressed through the "Kotaku" Program is Karangwaru Village, TegalrejoDistrict, Yogyakarta City. Karangarangwaru is a slum area before, and now has beentransformed into a safe, clean and comfortable area. The Kali Buntung River that passesthrough it has been revitalized so that the river water no longer overflows, and is able toaccommodate high-intensity rainwater. Other that, river access is also used as a rivermaintenance route. The city without Slums Program in Karangwaru Village can be said to havebeen well proven by the development and replica of the program carried out by the community.However, assistance is still needed by both the Consultant and the local government for BKMso that the program will continue to be implemented and better.Keyword : Community Development, Kotaku Program, Karangwaru village